STRENGTHENING THE HOUSEHOLD ECONOMY THROUGH THE ROLE OF WOMEN ON THE COAST OF THE ROKAN RIVER ROKAN HILIR REGENCY - Misdawita Misdawita (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
The sturdy economic pressure on the coastal area urges the exploitation of child labor and women. The state of poverty that is experienced by the paupers leads to the formation of intergenerational inheritance of poverty. The role of women is crucial in strengthening the household economy specifically in rural areas. Therefore, this study aims to ascertain the role of women on the coast of the Rokan River in assisting the household economy and what factors influence this role in strengthening the household economy. The variable of the role of women in this study is work decisions. This study uses logistic regression for its approach. The dependent variables assume Y=1 if women decide to work and Y=0 if women decide not to work. The variable of education level and husband income influence the women's decision to work while the variable of marital status, age, the number of toddler ownership, and the number of dependents do not influence the women's decision to work. The education level and husband income variables have an odd ratio of around 2,161 and 0,917 which means if the education level increases by 1 level, then the women's opportunity to work increases by 2,161 times, and if the husband's income increases by Rp.100.000, then the women’s opportunity to work increases by 0,917 times.